2023
DOI: 10.1038/s42003-023-04706-4
|View full text |Cite
|
Sign up to set email alerts
|

PIEZO1 and PECAM1 interact at cell-cell junctions and partner in endothelial force sensing

Abstract: Two prominent concepts for the sensing of shear stress by endothelium are the PIEZO1 channel as a mediator of mechanically activated calcium ion entry and the PECAM1 cell adhesion molecule as the apex of a triad with CDH5 and VGFR2. Here, we investigated if there is a relationship. By inserting a non-disruptive tag in native PIEZO1 of mice, we reveal in situ overlap of PIEZO1 with PECAM1. Through reconstitution and high resolution microscopy studies we show that PECAM1 interacts with PIEZO1 and directs it to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 83 publications
1
26
0
Order By: Relevance
“…50 dynamics. 55,61,67,68 By initiating localized force-dependent Ca 2+ entry at cell-cell junction, PIEZO1 channels participate in the formation and remodeling of adherens junctions. 61 PIEZO1 channels are also required for leukocyte diapedesis, the movement of leukocytes out of the vascular system.…”
Section: Piezo1 Regulates Adherens Junctions At Endothelial Barriermentioning
confidence: 99%
See 3 more Smart Citations
“…50 dynamics. 55,61,67,68 By initiating localized force-dependent Ca 2+ entry at cell-cell junction, PIEZO1 channels participate in the formation and remodeling of adherens junctions. 61 PIEZO1 channels are also required for leukocyte diapedesis, the movement of leukocytes out of the vascular system.…”
Section: Piezo1 Regulates Adherens Junctions At Endothelial Barriermentioning
confidence: 99%
“…55,61,67,68 By initiating localized force-dependent Ca 2+ entry at cell-cell junction, PIEZO1 channels participate in the formation and remodeling of adherens junctions. 61 PIEZO1 channels are also required for leukocyte diapedesis, the movement of leukocytes out of the vascular system. 67 Leukocyte-induced clustering of ICAM-1 (intercellular adhesion molecule-1) at EC surface generates mechanical forces that synergize with low shear stress to activate endothelial PIEZO1.…”
Section: Piezo1 Regulates Adherens Junctions At Endothelial Barriermentioning
confidence: 99%
See 2 more Smart Citations
“…Apical shear forces are known to be present for example in the endothelium from blood and lymph flow, and Piezo1 channels have been shown to sense these apical shear forces. [68,84] Basal mechanical cell-ECM interactions are known to play a role in, for example, cancer progression and development, but the details of this mechanical coupling are mostly unknown. In recent work, Ellefsen et al [83] showed that Piezo1 channels are localized evenly throughout the basal membrane but show most activity near focal adhesions.…”
Section: Mechanosensitive Piezo1 Channels Have a Major Role Inmentioning
confidence: 99%